Protective Effect of Baccharis trimera Extract on Acute Hepatic Injury in a Model of Inflammation Induced by Acetaminophen - Pádua, Bruno da Cruz; Rossoni Júnior, Joamyr Victor; de Brito Magalhães, Cíntia Lopes; Chaves, Míriam Martins; Silva, Marcelo Eustáquio; Pedrosa, Maria Lucia; Souza, Gustavo Henrique Bianco de; Brandão, Geraldo Célio; Rodrigues, Ivanildes Vasconcelos; Lima, Wanderson Geraldo; Costa, Daniela Caldeira (Mediators of Inflammation, 2014)
Background. Acetaminophen (APAP) is a commonly used analgesic and antipyretic. When administered in high doses, APAP is a clinical problem in the US and Europe, often resulting in severe liver injury and potentially acute liver failure. Studies have demonstrated that antioxidants and anti-inflammatory agents effectively protect against the acute hepatotoxicity induced by APAP overdose. Methods. The present study attempted to investigate the protective effect of B. trimera against APAP-induced hepatic damage in rats. The liver-function markers ALT and AST, biomarkers of oxidative stress, antioxidant parameters, and histopathological changes were examined. Results. The pretreatment with B. trimera attenuated serum activities of ALT and AST that were enhanced by administration of APAP. Furthermore, pretreatment with the extract decreases the activity of the enzyme SOD and increases the activity of catalase and the concentration of total glutathione. Histopathological analysis confirmed the alleviation of liver damage and reduced lesions caused by APAP. Conclusions. The hepatoprotective action of B. trimera extract may rely on its effect on reducing the oxidative stress caused by APAP-induced hepatic damage in a rat model. General Significance. These results make the extract of B. trimera a potential candidate drug capable of protecting the liver against damage caused by APAP overdose.